PERAN WANITA TANI DALAM MEWUJUDKAN KETAHANAN PANGAN RUMAH TANGGA DI KABUPATEN BANYUMAS (Studi Kasus di Kecamatan Cilongok) - ALTRI MULYANI; ALPHA NADEIRA MANDAMDARI (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2012)
The role of a woman in the household has a strategic position in maintaining household food security. A woman has an important role in selecting food to process them into food for the household. This research was aimed at recognizing: (1) Household food security condition of women peasant in Banyumas Regency; (2) The Factors that influenced the role of women peasant in efforts to achieve food security at household level in Banyumas Regency, and (3) The Factors that influenced the thediversivication patterns in Banyumas regency.